Do Environmental Management Systems, Environmental Performance, and Firm Size Influence Greenhouse Gas Emission Disclosures? - Wulansari, Neng Elga; Maysaroh Chairunnisa, Nurlaila; Susanti, Neneng Lasmita (Research of Finance and Banking, 2023)
This study aims to investigate whether the variables related to environmental management systems, environmental performance, and company size impact the reporting of greenhouse gas emissions. This research adopts a quantitative approach, utilizing secondary data from annual and sustainability reports selected through purposive sampling. Information was gathered from official company websites and the Indonesian Stock Exchange (BEI). The study encompasses 68 samples from an unbalanced panel data set of 28 companies from 2019 to 2021. The analytical methodology employed in this research involves panel data regression analysis. The results indicate that environmental management system variables and company size do not significantly influence greenhouse gas emission disclosures. However, it was observed that company size does have a notable positive effect on reporting greenhouse gas emissions. These findings offer valuable insights for governments and other institutions aiming to enhance environmental policies and foster improved greenhouse gas emission transparency within the industrial sector.